Catalyst-free cycloaddition of 1, 3-diene-1-carbamates with azodicarboxylates: A rapid click reaction. Issue 12 (15th June 2019) - Varlet, Thomas; Levitre, Guillaume; Retailleau, Pascal; Masson, Géraldine
Graphical abstract: Abstract: Novel click reactions are of continued interest in many scientific research areas and applications. Herein, we report a novel practical, catalyst-free, azo-Diels-Alder reaction between dienecarbamates and azodicarboxylates exhibiting a remarkable functional group tolerance. The availability of starting materials, mild reaction conditions, chemoselectivity and scalability make this cycloaddition a viable supplement to the other reactions in "click" chemistry.